Kemampuan Pemecahan Masalah, Pemikiran Kritis, dan Perilaku Inovasi Sarjana Strata Satu [Problem-Solving Ability, Critical Thinking, and Innovation Behavior of College Graduates] - Franklin, Franklin; Layman, Chrisanty (Universitas Pelita Harapan, 2021)
During their studies, students get various knowledge and abilities both general to specific in their field of interest. This knowledge will be used when faced with problems in the professional working world. But how much of it contributes to graduates behaviors in the workplace? This study aims to provide an overview of the relationship between Problem Solving, Critical Thinking, Communication, and Teamwork abilities in the practice of Innovation within the company. The study uses is a quantitative research method using a questionnaire conducted during the COVID-19 pandemic, distributed via Google Forms. The study was conducted with a population of undergraduate graduates in Indonesia who are already working, with a target of 205 respondents. Data processing that includes measurement models and structural models is carried out with the help of IBM SPSS AMOS 22.0 software. The results of the study indicate that there is a significant positive relationship between each independent variable on the dependent variable used, namely Innovation.BAHASA INDONESIA ABSTRAKMahasiswa selama berkuliah mendapat berbagai pengetahuan dan kemampuan baik yang sifatnya mendasar maupun lebih spesifik ke bidang peminatannya. Pengetahuan ini yang nantinya akan digunakan ketika dihadapkan pada masalah di dunia kerja. Namun berapa banyak dari hal ini berkontribusi kepada lulusan sarjana ketika memasuki lapangan pekerjaan? Pada penelitian ini bertujuan untuk memberikan suatu gambaran akan hubungan kemampuan Problem Solving, Critical Thinking, Communication, dan Teamwork pada praktik Innovation di perusahaan. Metode penelitian yang digunakan adalah metode penelitian kuantitatif yang menggunakan kuesioner saat pandemi COVID-19 disebarkan via Google Forms. Penelitian dilakukan dengan populasi alumni Strata Satu di Indonesia yang sudah bekerja, dengan target sebanyak 205 responden. Pengolahan data yang mencakup model pengukuran dan model struktural dilakukan dengan bantuan perangkat lunak IBM SPSS AMOS 22.0. Hasil dari penelitian menunjukkan bahwa terdapat hubungan signifikan positif antara masing-masing variabel bebas terhadap variabel terikat yang digunakan yaitu Innovation.